Gut microbial translocation corrupts myeloid cell function to control bacterial infection during liver cirrhosis. Issue 3 (18th July 2016) - Hackstein, Carl-Philipp; Assmus, Lisa Mareike; Welz, Meike; Klein, Sabine; Schwandt, Timo; Schultze, Joachim; Förster, Irmgard; Gondorf, Fabian; Beyer, Marc; Kroy, Daniela; Kurts, Christian; Trebicka, Jonel; et al.
Abstract : Objective: Patients with liver cirrhosis suffer from increased susceptibility to life-threatening bacterial infections that cause substantial morbidity. Methods: Experimental liver fibrosis in mice induced by bile duct ligation or CCl4 application was used to characterise the mechanisms determining failure of innate immunity to control bacterial infections. Results: In murine liver fibrosis, translocation of gut microbiota induced tonic type I interferon (IFN) expression in the liver. Such tonic IFN expression conditioned liver myeloid cells to produce high concentrations of IFN upon intracellular infection with Listeria that activate cytosolic pattern recognition receptors. Such IFN-receptor signalling caused myeloid cell interleukin (IL)-10 production that corrupted antibacterial immunity, leading to loss of infection-control and to infection-associated mortality. In patients with liver cirrhosis, we also found a prominent liver IFN signature and myeloid cells showed increased IL-10 production after bacterial infection. Thus, myeloid cells are both source and target of IFN-induced and IL-10-mediated immune dysfunction. Antibody-mediated blockade of IFN-receptor or IL-10-receptor signalling reconstituted antibacterial immunity and prevented infection-associated mortality in mice with liver fibrosis. Conclusions: In severe liver fibrosis and cirrhosis, failure to control bacterial infection is caused by augmented IFN and IL-10 expression that incapacitates antibacterial immunity of myeloid cells. Targeted interference with the immune regulatory host factors IL-10 and IFN reconstitutes antibacterial immunity and may be used as therapeutic strategy to control bacterial infections in patients with liver cirrhosis.